Prognostic factors in real-world elective supported high risk percutaneous coronary intervention with pLVAD or ECMO. (2nd May 2022) - Antunez Ballesteros, M; Alonso Fernandez De Gatta, M; Diego Nieto, A; Merchan Gomez, S; Garcia Monsalvo, M; Blanco Fernandez, F; Elvira Laffond, A; Cabanas Tendero, O; Oviedo Rodriguez, JD; Nunez Garcia, JC; Barrio Rodriguez, A; Martin Herrero, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): University Hospital of Salamanca - contract (CM19/00055) supported by the Instituto de Salud Carlos III in Spain (Co-funded by European Social Fund "Investing in your future"). Background/Introduction: Percutaneous coronary intervention (PCI) is the last remaining revascularization option in high risk (HR) patients affected by complex coronary artery disease not suitable for surgery. Elective mechanical circulatory support (MCS) could be necessary to keep hemodynamics during these procedures. In this context, selection of the patients balancing the risk-benefit is a challenge. Purpose: Analyse the factors related to mortality in patients who underwent elective HR-PCI with MCS: veno-arterial extracorporeal membrane oxygenation (VA-ECMO), Impella CP® or percutaneous heart pump (PHP). Methods: The study is a retrospective single centre registry, including all elective MCS implants for HR-PCI in a referral hospital. All of them were previously discussed in clinical session, deciding this modality of intervention by the Heart Team. Univariate analysis of variables related to discharge survival was performed using SPSS Statistics. Results: Twenty-seven patients underwent supported elective HR-PCI from 2013 to Sep-2021 (Figure 1). They were patients with low LVEF, high percentage of admission for ACS or HF, high coronary anatomy complexity (mean syntax score 31.4±9.5), and high surgical risk (mean STS morbidity-mortality score 24.17±16.0). In 88.9% of the patients, the circulatory support device was removed after completing the procedure, remaining in the rest due to persistent instability. The main access site was femoral, using axillary arterial access when the iliofemoral arteries were not suitable. Endotracheal intubation was needed in 29.6% of patients. Deaths during the admission (14.8%) were not directly related with the procedure but with posterior complications (alveolar haemorrhage, multiorgan failure, refractory heart failure and sepsis). Variables related to mortality were concomitant more than mild valvular heart disease; higher creatinine serum levels and lower pH before the procedure; axillary access and need for endotracheal intubation during or after the intervention; periprocedural mayor and minor bleeding and postprocedural critical care infections (Figure 1). We did not find other differences in terms of baseline characteristics, complexity of revascularization, type of support or development of complications. In the follow-up (median 4.8 [29.7] months) 70.4% of patients remain alive after the intervention (Figure 2). Conclusion: Temporary MCS used prophylactically in elective high-risk PCI appeared feasible and safe in the real-world setting and could be an alternative for patients dismissed for surgery because of high-risk. Moreover, we found some prognostic variables related to discharge survival to help clinicians with the selection of the most appropriate patients. Randomized studies are required to determine a better selection of cases according to risk-benefit